Role of gut microbiota and metabolomics in the lipid-lowering efficacy of statins among Chinese patients with coronary heart disease and hypercholesterolemia - Hu, Lihua; Hu, Boxian; zhang, Long; Hu, Yuhong; Zhang, Yali; Zhang, Ruihang; Yu, Hongxi; Liu, Dan; Wang, Xiaolei; Lin, Ouya; Gong, Yanjun; Zhang, Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundStatins, being the primary pharmacological intervention for hypercholesterolemia, exhibit a notable degree of interpatient variability in their effectiveness, which may be associated with gut microbiota. This study sought to identify the biomarkers for evaluating differences in statin efficacy.MethodsA quasi case-control study was conducted among participants with hypercholesterolemia and coronary heart disease taking rosuvastatin essential. According to the level of low density lipoprotein cholesterol (LDL-C), participants was divided into the “Up to standard” (US) group and the “Below standard” (BS) group. 16S rDNA sequencing and untargeted metabolomics were applied to detected the information of gut microbiota and related metabolites.ResultsA total of 8 US and 8 BS group matched by age and sex were included in the final analysis. 16S rDNA sequencing results indicated that the characteristic strains of the US group were f-Eubacterium_coprostanoligenes and g-Papillibacter, while the characteristic flora of the BS group were o-C0119, g-Pseudolabrys, s-Dyella-Marensis and f-Xanthobacaceae. Metabolomic results suggested that the levels of chenodeoxycholic acid-3-β-D-glucuronide, 1-methylnicotinamide and acetoacetate in stool samples of the US group were significantly higher than those of the BS group. By identifying the differentially abundant bacterial taxa, the gut microbiota could modulate the efficacy of statins through producing enzymes involved in cholesterol metabolism.ConclusionsThe findings suggest that the difference in statin efficacy may be related to gut microbiota strains that can produce short-chain fatty acids and secondary bile acids and affect the efficacy of statins by regulating the activities of cholesterol metabolite-related proteins. Metabolites related to short-chain fatty acids and secondary bile acids in the gut are expected to be biomarkers indicating the efficacy of statins.